2021
DOI: 10.3390/polym13213803
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Self-Healing Polyurethane Powder Coating Using Diels–Alder Reaction

Abstract: Although powder coating systems offer many environmental, ecological and energy related benefits over liquid based coatings, in the case of uretdione based polyurethane systems, high curing temperature is still an issue. On the other hand, powder coating systems make it possible to reduce the costs and enhance the process of forming complex 3D structures using the deep drawing method by pre-coated metal substrates. During this processing method, there is a probability of micro crack formation in the coated fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It is generally used to evaluate the self-healing performance of coatings. [73][74][75] (2). Analysis of chemical or elemental composition: includes analysis with Energy Dispersive X-ray Spectroscopy (EDS/EDX), X-ray Photoelectron Spectroscopy (XPS) and electron microprobe analysis (EPMA).…”
Section: Smart Self-healing Coatings On Magnesium-based Biomaterialsmentioning
confidence: 99%
“…It is generally used to evaluate the self-healing performance of coatings. [73][74][75] (2). Analysis of chemical or elemental composition: includes analysis with Energy Dispersive X-ray Spectroscopy (EDS/EDX), X-ray Photoelectron Spectroscopy (XPS) and electron microprobe analysis (EPMA).…”
Section: Smart Self-healing Coatings On Magnesium-based Biomaterialsmentioning
confidence: 99%
“…Self-healing polyurethane (PU) materials are a type of functional polymer with remarkable characteristics and potential. Based on their ability to spontaneously repair physical damage and restore their original functionality and structure, they have gained widespread appeal in emerging fields such as coatings, wearable electronic devices, , biomedical materials, and aerospace . By the incorporation of self-healing properties into polymer chains, these materials not only enhance their lifespan and broaden their applications but also facilitate easier maintenance and contribute to environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…A healing PU powder coating system containing a commercial uretdione-based cross-linker (BF1320), OH-functionalized polyester resin, and a Diels–Alder adduct as a healing agent is reported. The system exhibited 100% healing of a crack within 12.5 min at 120 °C [ 19 ]. Behera et al reported a dual-functional (PU) elastomer having disulfide as well as furfuryl functionalities to introduce healing properties.…”
Section: Introductionmentioning
confidence: 99%